PEMBINAAN AKHLAK PADA PESERTA DIDIK MELALUI KEGIATAN EKSTRAKURIKULER DI MTsN 6 AGAM - Resky Putra Hrp; Bambang Trisno; Rahmadani Rahmadani (CV. ADIBA AISHA AMIRA, 2023)
The development of morals in students is an important aspect of education at Madrasah Tsanawiyah Negeri (MTsN) 6 ​​Agam Kubang Putih. The success of this moral development can be achieved through various extracurricular activities specifically designed to develop students' character and morality. This research aims to evaluate the effectiveness of extracurricular activities in developing student morals at MTsN 6 Agam. The research method used is a descriptive method with a qualitative approach. Data was collected through observation and interviews. Research participants involved students, extracurricular supervisors, and school principals. The research results show that extracurricular activities at MTsN 6 Agam have a significant role in developing student morals. Activities such as self-development, religious studies, social activities, and teamwork make a positive contribution to instilling moral and ethical values ​​in students. Apart from that, student participation in these activities also increases their involvement in positive activities in the school and community environment. However, this research also identified several challenges in implementing moral development through extracurricular activities, such as limited resources and time. Therefore, it is recommended that schools continue to evaluate and improve in designing extracurricular activities that are more effective and sustainable in developing student morals.